PENGARUH PEMAHAMAN, KESADARAN WAJIB PAJAK DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK PRIBADI DI BATAM - Linda, Emilia; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2024)
The taxpayer compliance in Batam City is still considered in low level. It reflects from the comparisonbetween the number of registered taxpayer and the actual number of taxpayers reporting Annual NotificationLetter / Surat Pemberitahuan Tahunan (SPT). This research aims to examine the influence of theUnderstanding on Taxation, the awareness of Taxpayers and the service quality at Tax Office towards theTaxpayers. This research takes datas samples from 101 respondents in Batam City who considered asindividual taxpayer by using survey method through questioners which have been fulfilled with the answersfrom the respondents. The technique of data analysis used in this research is the validity test, reliability test,classical assumption test, multiple linear regression, t test, f test and determination coefficient test. As theresult, this research finds that the impact of Understanding on Taxation and the service quality at Tax Officebrings positive and significant effect on taxpayer’s compliance. However, Taxpayer awareness does notbring significant effect on Taxpayer’s compliance.Keywords: Understanding on Taxation, awareness of Taxpayer, service quality and the compliance ofTaxpayer.